2014
DOI: 10.1097/jcp.0000000000000228
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Topiramate in Alcohol Dependence

Abstract: Despite the small sample size and the short follow-up period, the present PLA-controlled study demonstrated the potential usefulness of TOP, even when administered at a dosage of 100 mg/d, for the treatment of detoxified alcohol-dependent subjects, confirming results from previous studies testing higher doses of TOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 49 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…This open-label study has been followed by a 6-week randomized placebo-controlled trial of low-dose topiramate (300 mg/day) for relapse prevention in 52 subjects with alcohol dependence post-detoxification [104]. Martinotti and colleagues [104] found that after 6 weeks of treatment, compared to placebo, those who received low-dose topiramate had fewer drinking days, less alcohol consumption, more days in treatment, reduced alcohol withdrawal and alcohol cravings, and reductions in mood and anxiety symptoms.…”
Section: Anticonvulsants For the Treatment Of Harmful Drinking Pattmentioning
confidence: 99%
“…This open-label study has been followed by a 6-week randomized placebo-controlled trial of low-dose topiramate (300 mg/day) for relapse prevention in 52 subjects with alcohol dependence post-detoxification [104]. Martinotti and colleagues [104] found that after 6 weeks of treatment, compared to placebo, those who received low-dose topiramate had fewer drinking days, less alcohol consumption, more days in treatment, reduced alcohol withdrawal and alcohol cravings, and reductions in mood and anxiety symptoms.…”
Section: Anticonvulsants For the Treatment Of Harmful Drinking Pattmentioning
confidence: 99%
“…Today, Phenytoin is not used for HPPD treatment due to its troubled side effect profile. Medications such as Valproic Acid (200–600 mg/day), Carbamazepine (200–600 mg/day), Oxcarbamazepine (300 mg/day), Gabapentin (300–900 mg/day), Topiramate (25–100 mg/day), and Lamotrigine (50–100) may be useful [ 23 ], also because of their efficacy in substance and alcohol use disorders [ 77 , 78 , 79 ]. In a single case of HPPD symptoms and electroencephalographic (EEG) abnormalities, compatible with toxic encephalopathy, the visual hallucinations that recurred at any alcohol ingestion improved, but did not disappear with the use of Valproic Acid (1500 mg/day) [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the faster titration schedule (eg, 5 weeks) of topiramate may have increased side effect burden and thus, the subsequent impact of adverse effects. 9 Prior studies have reported a greater frequency of adverse events with increased dosing of topiramate suggesting that adopting a slower titration schedule (eg, 8 weeks) may be ideal. 10 …”
Section: Discussionmentioning
confidence: 99%
“…9,10 Given that we did not evaluate craving typology in this study, it is possible that we included participants in this study who were less likely to benefit from treatment with topiramate. Another limitation pertains to the interpretation of study data.…”
Section: Discussionmentioning
confidence: 99%